ANDROID-BASED NATURAL DISASTER EVACUATION APPLICATION - Susilawati, Eva; Saniah, lia; Sahrial, Rysa; Muslim, Buhori (International Conference on Health Science, Green Economics, Educational Review and Technology, 2022)
Cianjur Regency is an area that is in the crust of the Sunda plate, and is right above the very active Cimandiri fault and stretches from Palabuhan Ratu, Sukabumi, Cianjur, Bandung to Cirebon Regency. At any time a shift (earthquake) and other natural disasters can strike, this is very important because the vast area of Cianjur stretches from south to north bordering Bogor, Bandung, and Sukabumi so applications such as preparedness efforts need to be made so that evacuation and coordination run smoothly if the facilities are not supported, the application for natural disaster evacuation uses an application platform that is widely used. Research using the Scrum Process application development method which is part of the agile development method, based on Scrum this process has produced research products in the form of applications that can be used by the BPBD in coordinating and evacuating refugees caused by disasters. so that all possibilities such as assisting can be carried out on target, providing information on the loss of refugee family members can be minimized, and so on being able to help BPBD coordinate everything.